Simbol Stratifikasi Sosial orang Muna dalam Tradisi Karia (Pingitan) di Desa Kafoo-Foo, Kecamatan KontukowunaOWUNA,KAB.MUNA - Nuria, Siti; Suraya, Rahmat Sewa; Rahman, Abdul; Almarsaban, Almarsaban (JURNAL KABANTI: Kerabat Antropologi, 2025)
This study is entitled “symbols of social stratification of Muna people in the karia (pingitan) tradition”. The purpose of this study is to find out the symbols of social stratification of muna people in the karia (pingitan) tradition and to describe the meaning contained in the karia (pingitan) tradition. Data collection in this study is direct research in the field using ordinary,observation methdos, ordinary interviews, and in-depth interfiews to data tracing. The result of this study indicate that the karia (pingitan) tradition contains symbols of markers between kaomu,walaka and maradika. where these markes can be seen at the time of kafoluku where there is a pitara. In the pitara there are parts that distinguish the groups, namely the kaomu group has two eggs on the head and two eggs on the feet. The walaka group has two eggs on the head and one egg on the foot and the maradika group has one egg on the head and one egg on the foot. Apart from that, in the karia (seclusion) tradition there are meanings contained such as  the meaning of pitara, facial makeup and bhoka (dowry)